Perceived Benefits and Barriers Related to Cervical Cancer Screening Among Married Women in Indonesia - Dora Samaria (NERS Jurnal Keperawatan, 2026)
Cervical cancer remains a significant public health issue in Indonesia including women in urban areas. Despite the availability of screening services in cities like Jakarta, Tangerang, Bekasi, and Depok, uptake remains low. Understanding how women perceive the benefits and barriers to cervical cancer screening is essential to improving participation rates. This study aimed to examine the perception of benefits and barriers related to cervical cancer screening among married women living in urban areas of Indonesia. A descriptive cross-sectional study was conducted among 748 married women aged 21–65 years in Jakarta, Tangerang, Bekasi, and Depok. Data were collected using a structured questionnaire and analyzed using descriptive statistics to summarize key variables, including educational level and employment status, income level, and perceptions of screening. The majority of participants had a low education level (78.6%), unemployed (77.7%), and social economy status below the regional minimum wage (86.1%). A total of 57% of respondents reported low perceived benefits of cervical cancer screening, and 48.5% perceived high barriers. Despite residing in urban areas with better access to healthcare, many women continue to hold limited poor perceptions about benefits of cervical cancer screening. These findings underscore the need for targeted health education, culturally sensitive interventions, and improved accessibility to increase screening uptake in Indonesia’s urban communities.